(untitled) (Global Journal of Management and Business Research, 2022)
The overarching goal of this study was to investigate the use of social networking sites in Kano manufacturing organizations and their impact on employee productivity, with a particular focus on HNL Manufacturing Company Kano. The study aimed to accomplish the following goals: to identify the use of social media networks in Kano manufacturing organizations; to investigate the impact of social networking sites on employee productivity at HNL Manufacturing Company; and to identify techniques that manufacturing organizations can use to increase employee productivity through social media networks. The analysis used a sample random sampling technique to implement a descriptive research design. The data collection method was carried out at HNL Company via an interview with a targeted sample size of 26 employees.